Monitoring Coral Reefs using the Transect Intercept Line Method in Coastal Mamboro, Taipa, Kayu malue and mamboro Villages After the 2 Year Tsunami of Palu City, Central Sulawesi Province. - Mohamad Akbar; Mohamad Musbah; Muliadin Muliadin; Alismi M Salanggon; Deddy Wahyudi; Renol Renol; Roni Hermawan (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Coral reefs are very important ecosystems and have a direct economic impact on coastal communities. In addition, coral reef ecosystems also play a role in providing habitat for various kinds of marine organisms such as Echinoderms, Crustaceans, Polychaeta, Chordata, Molluscs, Annelids and free-living marine biota such as plankton and fish. Over-exploitation of coral reefs and their resources, changes in top land that cause sedimentation and other anthropogenic activities will cause damage to coral reefs. Increasing pressure can threaten the existence and sustainability of coral reef ecosystems and the biota that live in them. In 2018 there was an earthquake 7.4 Richter scale accompanied by tsunami, the impact was large of destruction of the aquatic biota habitat of coral reef ecosystem. The aims of this study were (1) to examine the condition of coral reefs in Palu Bay, (2) to examine the composition of coral reefs in Palu Bay. Coral reef data was collected using the Line Intercept Transect (LIT) method. For coral reef observations using a transect with a length of 25 m, with every 50 cm observations or 50 points/transect. Each location were carried out 2 times. The results obtained shown the growth conditions of live coral were poor, but coral growth has started to improve. For water quality, it shown that the water quality in Palu Bay was suitable for coral reefs growth.